Applied Process Design for Chemical and Petrochemical Plants - Ludwig, Ernest E. (1964)
Contiene: Process Planning, Scheduling, Flowsheet Design; Fluid Flow; Pumping of Liquids; Mechanical Separations; Mixing of Liquids; Ejector and Vaccum Systems; Pressure-Relieving Devices